Pemanfaatan Media Sosial Tik-Tok Sebagai Media Dakwah (Analisis Pada Akun @ KADDAM) - Nuraini, Siti; Septia, Dini; Ulandari, Ulandari; Azwar, Khairul; Lubis, Nikmah (CV. PUSDIKRA MITRA JAYA, 2025)
Technological progress is concrete evidence in life in the modern era. Its urgency has spread widely to various fields. One of them is social media. Social media is one source of information used by the wider community. Nowadays, social media is considered a necessity in life. It cannot be denied that the function of social media is used as a form of convenience in providing or obtaining information covering several aspects, especially in the religious field. Islam utilizes the existence of social media as a means of da'wah. to facilitate and expand regional coverage in accepting Islamic teachings. The research method used is a qualitative method with a library research approach based on previous research. The results of this research state that all ulama agree with the use of social media as a means of da'wah by paying attention to the ethics and norms of using social media. This is believed to be a form of spreading Islamic teachings so that the messages conveyed spread easily. TikTok, which was initially known as an entertainment and trending platform, has now also become a place for Islamic da'wah content that is packaged creatively and lightly. Many da'wah accounts have emerged with a more relaxed, relatable, and communicative approach, so that they are able to reach the youth segment effectively.